Design Of Waste Management Model With Grounded Theory(Case Study: Isfahan) - farshid aslani (اکولوژی انسانی, 2023)
Simultaneously with the growth of communities and changing the consumption pattern of citizens, the process of urban waste management must adapt to these changes and design and implement alternative and more up-to-date procedures. Population growth, changing consumption patterns and lifestyles have increased waste production, types and variety of waste characteristics. Accordingly, the purpose of this study was to develop and explain the model of waste management in the metropolis of isfahan. The present study was conducted with a qualitative approach and data foundation theorizing method to design the model and purposeful sampling was used. The research tool was a semi-structured interview that was conducted between 12 experts of the isfahan metropolitan waste management organization.The results showed that the central phenomenon in the field of waste management is the lack of integrated management in this process, which needs to be solved in order to progress and develop the organization and move towards predetermined goals and strategies.lack of integrated management, as a core phenomenon due to lack of attention to managerial stability, lack of attention to research and development results, unpreparedness and lack of management and structural infrastructure will be formed as causal conditions.Waste management will have both positive and negative consequences.however, in this model, context conditions (such as sustainable development, education and culture building, encouragement and punishment, private sector investment and macro-policy) and intervening conditions (such as modern technologies, high exchange rates and sanctions, cheap energy and legal tools) affect relationships